Bridging algebra and sustainability: Examining the effectiveness of problem-based learning with Wizer.me in SDG 12-contextualized mathematics instruction - Suryawati Suryawati; Rika Murida Putri; Elizar Elizar (International Journal of Mathematics and Sciences Education, 2025)
Persistent challenges in algebraic learning among Indonesian junior high school students, characterized by performance below minimum mastery criteria, necessitate innovative pedagogical interventions. This study examined the effectiveness of integrating Problem-Based Learning (PBL) with the wizer.me digital platform in enhancing Year 7 students’ algebraic competence within the context of Sustainable Development Goal 12 (sustainable consumption and production). Employing a quantitative one-shot case study design, the research involved 24 randomly selected students from a junior high school in Banda Aceh during the 2024/2025 academic year. Data were collected through a validated post-test instrument comprising four essay questions contextualized within SDG 12 scenarios, assessing conceptual understanding, mathematical modeling, and problem-solving skills. Statistical analyses revealed significant learning outcomes, with students achieving a mean score of 76.33 (SD = 9.78), substantially exceeding minimum mastery criteria (t = 38.224, p < 0.001). Results demonstrate that the synergistic combination of PBL, interactive digital technology, and authentic sustainability contexts effectively facilitates algebraic mastery while cultivating global citizenship awareness. These findings suggest that educators should integrate technology-enhanced problem-based approaches and SDG frameworks into mathematics curriculum to enhance engagement, conceptual understanding, and real-world relevance. Future research should employ larger samples and experimental designs to establish robust causal evidence regarding the scalability and long-term impacts of such interventions.